The effects of caveolin1 on Î² cell proliferation - Li, Haicheng; Peng, Hangya; Xu, Haixia; Xu, Fen; Lin, Shuo; Lin, Keyi; Zeng, Wen; Zeng, Longyi (Cellular and Molecular Biology, 2018)
Our study aims to access the influence of caveolin1 (CAV1) on Î² cell expression profiles. We knocked down the expression of CAV1 in both NIT-1 cells and islets isolated from C57BL/6J mice using an RNA interference technique, which was realized by the transfer of an shRNA vector targeting CAV1 mRNA into NIT-1 cells or islets through latent virus infection. First, we identified the change in gene expression profiles in islets, in which the CAV1 expression level was down-regulated, as ascertained by mouse gene expression microarray, and the results showed that pathways related to Î² cell proliferation and pancreatic secretion functions were significantly influenced. The results of MTT demonstrated that the knockdown of CAV1 expression in NIT-1 cells promoted proliferation. The protein array results showed that pro-apoptotic cytokines were down-regulated in the NIT-1 cell line with CAV1 knockdown. These findings suggest that CAV1 might be involved in apoptosis and proliferation regulation in Î² cells, and therefore could be a potential target for the development of novel therapies for diabetes mellitus.